P307 TMS-based cortical mapping in double-arm transplantation. Issue 9 (September 2017) - Gök, Kadir; Döğer, Ela Naz; Göztepe, Mehmet Berke; Uysal, Hilmi; Özkan, Özlenen; Özkan, Ömer; Şenol, Utku; Doğan, Ebru Apaydin; Barçin, Ebru; Bilge, İnci; Şavkliyildiz, Ayhan; Carlak, Hamza Feza; et al.
Abstract : The re-adaptation process that the brain exhibits as a response to the environmental modifications resulting from prolonged or sudden limb loss can be described as a part of brain plasticity. In some cases, due to neurons synaptic interaction with neighboring neurons, motor-sensory representation of a hand can be replaced. In this study, it is aimed to develop neurophysiologic approaches for identification and discovery of structural and functional, transient and permanent plastic changes in arm-transplant cases. Abductor Pollicis Brevis (APB) and Orbicularis Oris (O. Oris) muscle representation mapping are performed using Transcranial Magnetic Stimulation (TMS) for a double-arm transplant. A control group is established to interpret the cortex map of the transplantation case. The position, amplitude, and latency values of the motor evoked potentials, which are generated by a magnetic stimulation, are determined by the developed software. Results are embedded on the designed 3D head model and the TMS map is created. Depending on results of the mapping, hotspot of the control group is found as C1(6.89( ± 1.67) mV–20.98( ± 0.87) ms) in the 10–10 system and hotspot of the hand mapping is C3(1 mV–38.9 ms). 85.48% decreases in amplitude and 85.41% increases in latency value occur in the hand mapping with respect to the control group. As a result of the comparison of the generated maps with the normal group, brain plastic change is observed in the double-arm transplant. Although the transplantation period of 1 year is yet to be completed, the brain adaptation is still proceeding. In this case, the hand representing area has spread towards the face representation area. This study is supported by TUBITAK with 215E012 project number.